Enhancing Parents’ Understanding through Educational Programs CAMPHAL - Dwi Setiowati; Istahlil Adam Hussein (LOSARI DIGITAL, 2026)
Measles remains a major public health issue in Indonesia, particularly in Muslim communities where vaccine hesitancy is influenced by limited knowledge and concerns regarding the halal status of vaccines. This community service program aimed to enhance parents’ knowledge about measles disease and the halal assurance of vaccines through the CAMPHAL (Campak and Kepastian Halal Vaksin) education model. A community-based participatory approach was implemented involving 15 mothers of toddlers in RW 01 Sari Mulya, Kelurahan Setu, South Tangerang. The program included interactive education sessions, pre-test and post-test assessments, and direct consultations. Results showed a significant increase in knowledge, with the mean score improving from 9.0 to 9.6 (the Wilcoxon Signed-Rank Test, p < 0.05). All participants achieved scores of 9 or above in the post-test, indicating reduced vaccine hesitancy and greater confidence in the halal permissibility of measles vaccines. This program demonstrates the effectiveness of integrating scientific and religious approaches in health education